Valorization of natural adsorbents for removing chromium (VI) from industrial wastewater: a review - Haroon, Hajira; Butt, Tayyab Ashfaq; Shah, Jehanzeb Ali; Ciobica, Alin; Romila, Laura Ecaterina; Burlui, Vasile; Bibi, Hamida; Bilal, Muhammad (Frontiers in Chemistry, 2025)
Chromium (Cr(VI)) is often released from various industries in excess in developing countries, which constitutes non-compliance with environmental regulations. This metal is hazardous for the aquatic ecosystem and is responsible for toxicity, carcinogenicity, and mutagenicity in humans. Adsorption is an effective and relatively inexpensive approach for treating the excess Cr(VI) compared to conventional methods. Commercially available adsorbents cannot be considered economical yet for industrial applications, which has alternatively resulted in the use of natural adsorbents. The current study focuses on Cr(VI) removal using low-cost natural adsorbents and discusses the different conditions used for such treatments. Previous studies have shown the following order of average Cr(VI) removal using different adsorbents: leaves > bark > agriculture > dry shell > tea = fungi > yeast > algae > sawdust > bacteria. Moreover, acid modification has been reported to offer the best results. The adsorption data are best fitted to both the Langmuir and Freundlich isotherms. Hence, the abovementioned low-cost natural biomasses hold promising potential for Cr(VI) removal from wastewater, whose removal efficiency can be improved by adopting economical and effective pretreatment techniques. Literature also shows that leaves are more efficient and economical for Cr(VI) removal without pretreatment from among the various available bulk biomasses. The present review is expected to provide guidance for low-cost treatment of Cr(VI) at the industrial scale.